Planning times of completion of censorship authorities for the department to checking activity financing, distribution in the Office of Financial Supervision Federal specimen using a general allocation with practical application - Abdel Moneim Kadhim Hammadi; Shaima Khazaal ShnesheeL (Journal of Madenat Alelem University College, 2017)
In this study, the refinancing for the distribution of censorship authorities on departments subject to the scrutiny of the Department of checking Activity Funding and distribution in the Office of Financial Federal censorship, it was constructing a model general allocation depending times completed regulatory authorities administrations controlled by to checked for 2016,Where it was building a mathematical model of the first group of authorities this department, and so to get optimal allocation for censorship authorities on Administrations The research aims to optimize distribution planning for censorship authorities Administrations and reduce the time of complete the work of censorship authorities and with authorities outputs (final account, accumulated account, the results of the work, contracts, manual report, evaluating performance, visitation, else) To Completion required for each authority for Checking authorities in the end of each year was used of linear programming method to solve the correct model general allocation and has been used to solve these mathematical models winQSB program. The researcher reached to the distribution of censorship Authorities are optimal and complete the work of authorities less as possible, and through applying models show that the total times for a total of achievement general for first group reached (16387). Day in year, while the total the times general and the planned duration same time period may toll of (16506). On the days in year a difference on (119) in year, On the days in year a difference On the days in year, This is evidence of examples of mathematical models for the allocation of on Censorship authorities Administrations subject for checking.